El partido PRO y el triunfo de la nueva derecha en Argentina - Ernesto Bohoslavsky; Sergio Morresi (Les Cahiers ALHIM)
This papers aims to identify the place held by the party Propuesta Republicana (PRO), which has obtained the presidency in 2015, in the history of Argentine right-wing parties. The meaningful organizational and ideological differences with previous rightist traditions, which were key for PRO to obtain electoral triumph will be shown. In the first section the main features of Argentine right-wing organizations in the 20th century such as electoral weakness and ability/skill to include their followers in several cabinets are presented. The second section refers to PRO’s leadership style, voters´ background and ideological profile. The third section compares the historical features of Argentine right-wing parties and PRO’s features. Our conclusions show that PRO has been successful for three main reasons: a) it was built as a willing-to-win party, which implied to resign to be an ideology-centered party and embrace pragmatism, b) leader and cadres recruitment without ideological criteria, which allowed to seduce die hard Peronist voters; c) a territorial expansion process combined with tactics and practices typical of professional-electoral political parties.